Mesenchymal hamartoma of the thoracic wall in an infant: Case report - Kazez, Ahmet; Yekeler, Hayreddin; Özel, Ş. Kerem; Solmaz, Özgen A.; Kocakoç, Ercan; Baykara, Murat (My University, 2005)
Mesenchymal hamartoma of thoracic wall (MHTW) in children is a very rare, benign lesion which has significance as it requires a wide resection for complete removal. MHTW was diagnosed in a five-month-old girl who was brought with the complaint of a mass on the right side of her thorax that was recognised two months ago. A thoracotomy, complete excision of the mass with two ribs and a two layered synthetic patch application for the defect on the thoracic wall was performed. The case was presented due to its rarity and to discuss the therapeutic approach.
Bebekte gö?üs duvarinin mezenkimal hamartomu: Olgu sunumu
Keywords: Hamartoma; Mesenchymal, chest wall, children